Degradation study of CuInSe2 thin films - Chang, Chung Bin (2013)
The degradation behavior of CuInSe2 thin film was studied in this project to understand the effects of high intensity light and corrosive acids on its structural,morphological, electrical and optical properties. Polycrystalline CuInSe2 thin film has been synthesized using thermal evaporation method and source material was produced by solid state reaction process of Cu, In, Se elements. The samples are in good agreement to the tetragonal structure of JCPDS data (Ref. 98-008-7482).Samples exposed to increasing light irradiance intensity from 250 to 1500W/m2 shows increment in crystallite sizes from 80.90 to 138.30nm. It was found out that the films were sensitive to light-induced heat which leads to heating effect and subsequently improves the films quality. Fine spherical or elliptical grains were observed in the AFM topography for all samples while the RMS roughness of the thin films slightly decreases from 14.72 to 10.64nm after the exposure to light and maintained relatively constant as the increase of light intensity. The sheet resistivity of samples after light exposure at all intensities increased from 1.3 x 10-3 to 3.7 x 10-3 Ωcm with intensity due to the increase of surface scattering effect and the increase of light-induced defects in the films which act as recombination center for electron-hole pair. The direct band gap of the samples increases from 1.52 to 1.59eV with the increasing of light intensity. For samples degraded in sulfuric acid, the crystal structures and RMS roughness of all samples remain relatively unchanged after the degradation which infers that the ions in sulfuric acid do not affect the crystal structure significantly. Nevertheless, for samples degraded in nitric acid, the FWHM values increase from 0.8346 to 1.2932 when the concentration of H+ and (NO3)- ions increases infers that the thin films’ quality degenerates. Both samples degraded in sulfuric and nitric acid shares similar trends in resistivity and band gap results. The resistivity of both samples increased with same magnitude of Δρ=0.4x10-3Ωcm due to the increase in hydrogen concentration whereby creates more copper vacancies and hence increases resistivity. The band gap for both samples decreased with a ΔEg=0.17eV with increasing concentration of hydrogen ions. The decrease of the optical band gap was due to the increase of copper vacancies concentrations. From aforementioned results, all samples subjected to light and acid degradation have an increase of resistivity after exposure. Nevertheless, light exposure dealt greater degradation to the resistivity of thin films than acid exposure with respect to the magnitude. These findings concluded that the effect of light degradations and acid degradations have a significant influence on the morphological, electrical and optical properties of CuInSe2 thin films and therefore the degradation behavior of CuInSe2 thin film is understood.